Link of gut microbiome with risk of type 2 diabetes mellitus - Alkhammash, Alhanouf M.; Alshehri, Wafa A.; Alhozali, Amani M.; Bahieldin, Ahmed (Journal of Contemporary Medical Sciences, 2022)
The gut microbiota presented in the human digestive system plays an active role in maintaining host health. Recent studies that rely on the use of high throughput metagenomic sequencing (MGS) revealed the association of dysbiosis in the intestinal microbial community and many chronic diseases, specifically type 2 diabetes (T2D). This disease is considered one of the most prevalent metabolic diseases worldwide comprising up to 90%. This article presents the most prominent research in this field and summarizes the method used to study the diversity of the gut microbiome through the use bioinformatics tools. We highlight the role of gut metabolic products in the development of T2D, as many studies have proven the influence of microbial metabolite products, such as LPS and SCFAs, on blood glucose levels through the microbial-host cross-talk. In addition, this article underlines the interaction of epigenetic mechanisms and the gut microbiome in regulating and developing T2D. The latter can be an appropriate preventative or therapeutic approach for several human metabolic diseases. Therefore, future research is required to build new type of T2D therapy based on epigenetic mechanisms, microbial composition, and microbial metabolites.